Giant esophageal lipoma: complicated surgical treatment (case report) - Katinaitė, Justina; Jagelavičius, Žymantas; Kybartas, Algis; Gruslys, Vygantas; Janilionis, Ričardas (Lietuvos chirurgija, 2017)
Background Lipomas are distinctly uncommon benign tumours of the esophagus. Lipoma and other benign tumours should be considered for patients admitted to the hospital with non-specific complaints of upper gastrointestinal tract disease. Radiological and endoscopic suspicion of a tumour with benign histology and correct preoperative histological diagnosis are important factors in order to choose the best surgical treatment option.Case report A 59-year-old woman was admitted with dysphagia lasting for about 1.5 months. Endoscopy and computed tomography scan revealed intraluminal pedunculated submucosal mass, 13 cm in length and 2 cm in diameter, –67 Hounsfield units in density, suggesting esophageal lipoma to be the most likely diagnosis. Tumour was excised through right lateral thoracotomy with esophagotomy. Barium esophagogram in the postoperative period showed esophageal leakage, hence rethoracotomy was performed and the defect was attempted to close by sutures. Repeated barium esophagogram revealed persisting evidences of esophageal leakage so biodegradable coated 10 cm in length and 31/25/31 mm in diameter SX-ELLA stent was used and successfully sealed the leakage.Conclusion Giant esophageal lipoma is a rare benign esophageal tumour causing dysphagia. Open surgery is the best treatment option for giant esophageal lipomas. However, postoperative complications such as esophageal leakage are common in patients after open esophageal surgery. Biodegradable stent could be successfully used dealing with persistent esophageal leakage.
Keywords: dysphagia; esophageal lipoma; esophagotomy; mediastinitis; esophagopleural fistula